Functional outcomes following immediate repair of penile fracture: a tertiary referral centre experience with 76 consecutive patients. (4th March 2017) - De Luca, Francesco; Garaffa, Giulio; Falcone, Marco; Raheem, Amr; Zacharakis, Evangelos; Shabbir, Majed; Aljubran, Abdelkareem; Muneer, Asif; Holden, Fiona; Akers, Claire; Christopher, Nim; Ralph, David J.
Abstract: Objective: The aim of this study was to report surgical and functional outcomes in patients who underwent immediate penile fracture repair following location of the tunical tear with ultrasonography. Methods: Patients' clinical notes from September 2005 to October 2015 were reviewed. The inclusion criteria were the documented presence of an albugineal laceration at the preoperative ultrasonography and during surgical exploration. In total, 76 patients were enrolled in the study. The aetiology, presentation, imaging results, intraoperative findings, functional outcomes and complications of surgical repair were retrospectively extrapolated from the clinical notes. Patients were questioned about their erectile and urinary function 12 months after the traumatic event. Validated questionnaires were administered to enquire about sexual and urinary function. Finally, the accuracy of the ultrasound in detecting the site of the tunical defect was evaluated. Results: The mean age was 39.5 years (range 21–72 years) and the median follow-up was 13 weeks. The aetiology of the fracture was sexual intercourse in 70 patients, the taqaandan manoeuvre in three and trauma while sleeping in three. The intraoperative findings showed a ventral and transverse tear in 93.5% of cases. Urethral injuries were evident in one-quarter of the patients. Ultrasonographic findings were confirmed intraoperatively in all patients. Worsening of the quality of erections was reported by 5% of patients, and 5.2% reported a penile curvature postoperatively. Conclusion: Penile fracture is a rare urological emergency and requires early surgical exploration and repair. Ultrasonography is a cheap and readily available investigation that allows confirmation of the diagnosis, and identification of the location of the tear and the associated urethral injury.